New Insights on Volatile Components of Vanilla planifolia Cultivated in Taiwan - Yeh, Chih-Hsin; Chen, Kai-Yi; Chou, Chia-Yi; Liao, Hsin-Yi; Chen, Hsin-Chun (Molecules (Basel, Switzerland), 2021)
Vanilla (Vanilla planifolia) is a precious natural flavoring that is commonly used throughout the world. In the past, all vanilla used in Taiwan was imported; however, recent breakthroughs in cultivation and processing technology have allowed Taiwan to produce its own supply of vanilla. In this study, headspace solid-phase microextraction (HS-SPME) combined with GC-FID and GC-MS was used to analyze the volatile components of vanilla from different origins produced in Taiwan under different cultivation and processing conditions. The results of our study revealed that when comparing different harvest maturities, the composition diversity and total volatile content were both higher when the pods were matured for more than 38 weeks. When comparing different killing conditions, we observed that the highest vanillin percentage was present after vanilla pods were killed three times in 65 °C treatments for 1 min each. From the experiment examining the addition of different strains, the PCA results revealed that the volatiles of vanilla that was processed with Dekkera bruxellensis and Bacillus subtilis was clearly distinguished from which obtained by processing with the other strains. Vanilla processed with B. subtilis contained 2-ethyl-1-hexanol, and this was not detected in other vanillas. Finally, when comparing the vanillin percentage from seven different regions in Taiwan, vanilla percentage from Taitung and Taoyuan Longtan were the highest.